2023
DOI: 10.1007/s00228-023-03467-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based medication adherence among seniors in the first year after heart failure hospitalisation and subsequent long-term outcomes: a restricted cubic spline analysis of adherence-outcome relationships

Abstract: Purpose Non-adherence to heart failure (HF) medications is associated with poor outcomes. We used restricted cubic splines (RCS) to assess the continuous relationship between adherence to renin-angiotensin system inhibitors (RASI) and β-blockers and long-term outcomes in senior HF patients. Methods We identified a population-based cohort of 4234 patients, aged 65–84 years, 56% male, who were hospitalised for HF in Western Australia between 2003 and 2008 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Use of GDMT at the time of enrolment (∼2 days before discharge from an AHF admission) was similarly sparse in both younger and older patients, except for beta‐blockers that were more frequently used by older individuals. Although the low utilization of GDMT in the current study before enrolment was part of the inclusion criteria for the study, registry data published previously have shown that in various regions of the world, prescription of and adherence to GDMT is significantly lower in older patients with AHF 12–17 …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Use of GDMT at the time of enrolment (∼2 days before discharge from an AHF admission) was similarly sparse in both younger and older patients, except for beta‐blockers that were more frequently used by older individuals. Although the low utilization of GDMT in the current study before enrolment was part of the inclusion criteria for the study, registry data published previously have shown that in various regions of the world, prescription of and adherence to GDMT is significantly lower in older patients with AHF 12–17 …”
Section: Discussionmentioning
confidence: 81%
“…Although the low utilization of GDMT in the current study before enrolment was part of the inclusion criteria for the study, registry data published previously have shown that in various regions of the world, prescription of and adherence to GDMT is significantly lower in older patients with AHF. [12][13][14][15][16][17] There is a common assumption that older age identifies a vulnerable population of patients. 18 Further, these patients may be even more susceptible in the early post-discharge phase.…”
Section: Discussionmentioning
confidence: 99%